The Trp73 Mutant Mice: A Ciliopathy Model That Uncouples Ciliogenesis From Planar Cell Polarity - Marques, Margarita M.; Villoch-Fernandez, Javier; Maeso-Alonso, Laura; Fuertes-Alvarez, Sandra; Marin, Maria C. (Frontiers in Genetics, 2019)
p73 transcription factor belongs to one of the most important gene families in vertebrate biology, the p53-family. Trp73 gene, like the other family members, generates multiple isoforms named TA and DNp73, with different and, sometimes, antagonist functions. Although p73 shares many biological functions with p53, it also plays distinct roles during development. Trp73 null mice (p73KO from now on) show multiple phenotypes as gastrointestinal and cranial hemorrhages, rhinitis or central nervous system defects. Several groups, including ours, have revisited the apparently unrelated phenotypes observed in total p73KO and revealed a novel p73 function in the organization of ciliated epithelia in brain and trachea, but also an essential role as regulator of ependymal planar cell polarity. Unlike p73KO or TAp73KO mice, tumor-prone Trp53-/- mice do not present ependymal ciliary or planar cell polarity defects, indicating that regulation of ciliogenesis and PCP is a p73-specific function. Thus, loss of ciliary biogenesis and epithelial organization might be a common underlying cause of the diverse p73KO-phenotypes, highlighting Trp73 role as an architect of the epithelial tissue. In this review we would like to discuss the data regarding p73 role as regulator of ependymal cell ciliogenesis and PCP, supporting the view of the Trp73-mutant mice as a model that uncouples ciliogenesis from PCP and a possible model of human congenital hydrocephalus.